Dichotomous preferences and power set extensions - Ritxar Arlegi; Dinko Dimitrov (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
This paper is devoted to the study of how to extend a dichotomous partition of a universal set X into good and bad objects to an ordering on the power set of X. We introduce a family of rules that naturally take into account the number of good objects and the number of bad objects, and provide axiomatic characterizations of two rules for ranking sets in such a context.
urn:nbn:de:bvb:19-epub-6431-5
Keywords: D81; 330; dichotomy; objects; set extensions; ranking sets; Präferenztheorie; Logik; Theorie